(3ZfjI GdHGMKs - (3GdQMHqj, GHf GdoerJpbnfI, CHh YHO Gddg, eMeO Hf Ydj Hf eMeO Hf GdMSf, (B577 (3g`s ((3CMeO GdShjaj GdhGUdj GdeGdcj GdCRgQjs)
(3ChdgG (B:s
(3HYO GdHSedI ; Chd eG fSJaJM GdebGd HPcQ MeO QHfG JYdi aGdMeO ddg Ydi eG CfYeG MeOG Hg jLdh Yf GdbdH GdYeis
(3BNQgG (B:s
(3aaj GdSgGe JVQH Chai hbaJgG JeGe agPg JeGe agPg WQjbI GdefGSNI aGQb HgG QJHJJg aVd TGeNIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6 / 279s
(3eYLe GdeDdajf (B3 / 537s
(3cTa GdXfhf (B2 / 1211s
(3gOjI GdYGQajf (B2 / 99s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdaQGFVs